If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = 3(6x + 15) Reorder the terms: 9x = 3(15 + 6x) 9x = (15 * 3 + 6x * 3) 9x = (45 + 18x) Solving 9x = 45 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 9x + -18x = 45 + 18x + -18x Combine like terms: 9x + -18x = -9x -9x = 45 + 18x + -18x Combine like terms: 18x + -18x = 0 -9x = 45 + 0 -9x = 45 Divide each side by '-9'. x = -5 Simplifying x = -5
| 8w=5w+21 | | 27y=13(2y+14) | | y/3+6=-1 | | m+1/7=-2 | | 4(3+5)-3= | | o=8x-69 | | 8-8=18x+11x | | 4+6x-5=14x+14-8x | | 90=4t-19t | | (N+5)N=150 | | 6+12x-2=15x+4-3x | | (x-9)(x-20)=0 | | 3N+6N=180 | | 3y-3=7+8y | | 4[5-4(4-t)]-2=5[4(5t-3)+9]-60 | | 7(3n+4)=9(7n+2)+2 | | 9y-9=-5(y+6) | | 7r-2p-4r+6p= | | 2w-3(w-8)=3(w+2)-2 | | 6000=l*60 | | 6x^2-5x+8=0 | | 5x^3-10x^2+3x-6=0 | | 4+2.8=6.8 | | X-2y-2z=-12 | | -21+30=-3y | | 4.2=t+1.8 | | 8-10x=27-17x | | -5y=75 | | 8x^2+20x+8=0 | | 6+t=14 | | 7-2a=7 | | m+17=33 |